The scope of the regression of the principle of criminal legality in exceptional circumstances - analytical research - Assistant Professor Dr. Muhammad Hamid Abd, (The college of law and political science journal, 2023)
Exceptional circumstances are the most prominent reasons for deviating from the scope of penal legitimacy, as they are, by virtue of necessity, resorting to those in charge of managing state affairs and those entrusted with them to preserve the interests of their people, to find alternatives and mechanisms that guarantee the preservation of those interests, or no less, that their essence be guaranteed, whatever the circumstances. And conditions, and given the importance of the criminal law and its great link to the rights and freedoms of individuals and the guarantee of the main interests in the state, and the ruling principles that guarantee the aforementioned interests, and foremost among them the principle of penal legality, we examined in this research the extent to which the stability of this principle was affected by the circumstances Exceptionalism, and whether it accepts re-reading and interpretation in a clear and correct way, and the variables that occur, and whether it can be said that the field of its application has declined under certain justifications, most of which fall under the heading of exceptional circumstances, and standing on the areas of that decline and the amount that is prevented from that (refusing to recede). The justifications were